2013
DOI: 10.1016/j.jradnu.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Dignity in Professional Nursing: Guaranteeing Better Patient Care

Abstract: Nursing professional dignity is a complex topic. This article describes intrinsic and professional nursing dignity and gives some historical background on nursing in Italy as the setting for a qualitative study of dignity conducted in the same country. The study results show the importance of recognition of nursing professional dignity as it relates to professional satisfaction and patient care. (J Radiol Nurs 2013;32:120-123.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The professional dignity of midwives is determined by their professional image and confirmed by other health professionals. 2 When midwives are supported and treated with respect, they have a positive experience of professional dignity and their professional dignity is enhanced. The opposite happens when they are not treated with respect.…”
Section: Professional Dignity Of Midwivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The professional dignity of midwives is determined by their professional image and confirmed by other health professionals. 2 When midwives are supported and treated with respect, they have a positive experience of professional dignity and their professional dignity is enhanced. The opposite happens when they are not treated with respect.…”
Section: Professional Dignity Of Midwivesmentioning
confidence: 99%
“…1 Respect for oneself and for others determines a person's professional dignity and is a prerequisite for the optimal functioning of the team. [2][3][4] Respect for others' professional dignity is as important as respect for your own professional dignity, creating work environments that are conducive for optimal patient care. 5,6 Hospital managers can also create environments conducive for the honouring of the professional dignity of the health team members.…”
Section: Introductionmentioning
confidence: 99%
“…Human dignity in Islam and the West means to value both oneself and others (Reshad, ; Stievano, Rocco, Sabatino, & Alvaro, ); however, their indicators are somehow different. In Islam, human dignity includes indicators such as freedom of soul and autonomy, whereas in the West freedom and human dignity are considered as distinctive value categories including indicators such as honor, confidentiality, and respect to life.…”
Section: Resultsmentioning
confidence: 99%
“…Human dignity, which is considered as the foundation of human rights, relies on the innate value of human being. Having an interactional nature, dignity means respect to inner freedom and responsibility for one's own and others' lives (Kangasniemi et al, 2013;Stievano et al, 2013).…”
Section: The Definitions Of Islamic and Western Ethical Values In Hmentioning
confidence: 99%
“…Moreover, Khademi et al (2012) identified the dignity violations as follows: “disrespect”, “coercion and violation of autonomy”, “ignoring professional and scientific capability” and “denying the value of nurse/care.” In this regard, Sabatino et al (2016) mentioned that the low number of nurses, insufficient time and excessive working hours reduce the respect for nurses' dignity and professional values. The results of a study by Stievano et al (2013) showed that nurses are dissatisfied with their work mainly due to a lack of respect for their professional dignity. They also emphasized the need for more research in other countries and different clinical settings better to understand the concept of nurse's professional dignity and its threatening factors.…”
Section: Introductionmentioning
confidence: 99%